Access to a Labile Monomeric Magnesium Radical by Ball-Milling - Jedrzkiewicz, Dawid; Mai, Jonathan; Langer, Jens; Mathe, Zachary; Patel, Neha; DeBeer, Serena; Harder, Sjoerd (Angewandte Chemie International Edition, 2022)
In order to isolate a monometallic Mg radical, the precursor (Am)MgI⋅(CAAC) (1) was prepared (Am=tBuC(N-DIPP)2, DIPP=2,6-diisopropylphenyl, CAAC=cyclic (alkyl)(amino)carbene). Reduction of a solution of 1 in toluene with the reducing agent K/KI led to formation of a deep purple complex that rapidly decomposed. Ball-milling of 1 with K/KI gave the low-valent MgI complex (Am)Mg⋅(CAAC) (2) which after rapid extraction with pentane and crystallization was isolated in 15 % yield. Although a benzene solution of 2 decomposes rapidly to give Mg(Am)2 (3) and unidentified products, the radical is stable in the solid state. Its crystal structure shows planar trigonal coordination at Mg. The extremely short Mg−C distance of 2.056(2) Å indicates strong Mg−CAAC bonding. Calculations and EPR measurements show that most of the spin density is in a π* orbital located at the C−N bond in CAAC, leading to significant C−N bond elongation. This is supported by calculated NPA charges in 2: Mg +1.73, CAAC −0.82. Similar metal-to-CAAC charge transfer was calculated for M0(CAAC)2 and [MI(CAAC)2+] (M=Be, Mg, Ca) complexes in which the metal charges range from +1.50 to +1.70. Although the spin density of the radical is mainly located at the CAAC ligand, complex 2 reacts as a low-valent MgI complex: reaction with a I2 solution in toluene gave (Am)MgI⋅(CAAC) (1) as the major product.
CRIS-Team Scopus Importer:2022-02-25
Keywords: DFT Calculations; EPRSpectroscopy; Low-Valent Complexes; Magnesium; Radicals

Formation and Reactivity of Non-Stabilized Monomeric Alumoxane Intermediates - Grams, Samuel; Maurer, Johannes; Patel, Neha; Langer, Jens; Harder, Sjoerd (Zeitschrift für Anorganische und Allgemeine Chemie, 2022)
Several methods for the oxidation of the β-diketiminate AlI complexes (BDI)Al and (BDI*)Al with O2, Et3P=O or N2O are presented (BDI=HC[C(Me)N(DIPP)]2, DIPP=2,6-diisopropylphenyl; BDI*=HC[C(tBu)N(DIPP)]2). The selectivity of alumoxane formation depends strongly on the nature of the β-diketiminate ligand, the experimental procedure and the solvent. The mononuclear alumoxanes (BDI)Al=O and (BDI*)Al=O are highly reactive intermediates that cannot be isolated but either aggregate to give less reactive dimers or decompose by internal C−H activation of a backbone Me group or an iPr group. Ethereal solvents like Et2O react with alumoxanes to give (BDI)Al(OEt)OH and ethylene by β-H elimination. In case of N2O oxidation, subsequent reaction with a second equivalent of N2O to form the hyponitrite complexes (BDI)Al(N2O2) and (BDI*)Al(N2O2) is observed. Details of the alumoxane formation, reactivity and decomposition have been obtained by DFT calculations. These calculations also underscore their rather bipolar character, represented by the resonance structure (BDI)Al+−O−, and estimate the σ- and π-bond character of the Al=O bond at circa 76 % and 24 %, respectively.
CRIS-Team Scopus Importer:2022-03-11
Keywords: Aluminium; Alumoxane; DFT calculations; Low-valent; β-diketiminate

On the existence of low-valent magnesium-calcium complexes - Mai, Jonathan; Rösch, Bastian; Patel, Neha; Langer, Jens; Harder, Sjoerd (Chemical Science, 2023)
DFT-Calculations predict that a low-valent complex (BDI)Mg-Ca(BDI) with bulky beta-diketiminate (BDI) ligands is thermodynamically stable. It was attempted to isolate such a complex by salt-metathesis between [((BDI)-B-DIPeP*) Mg-Na+](2) and [((BDI)-B-DIPeP)CaI](2) ((BDI)-B-DIPeP = HC[C(Me)N-DIPeP](2); (BDI)-B-DIPeP* = HC [C(tBu)N-DIPeP](2); DIPeP = 2,6-CH(Et)(2)-phenyl). Whereas in alkane solvents no reaction was observed, salt-metathesis in C6H6 led to immediate C-H activation of benzene to give ((BDI)-B-DIPeP*) MgPh and ((BDI)-B-DIPeP) CaH, the latter crystallizing as a THF-solvated dimer [((BDI)-B-DIPeP) CaHTHF](2). Calculations suggest reduction and insertion of benzene in the Mg-Ca bond. The activation enthalpy for the subsequent decomposition of C(6)H(6)2(-) into Ph- and H- is only 14.4 kcal mol(-1). Repeating this reaction in the presence of naphthalene or anthracene led to heterobimetallic complexes in which naphthalene(2-) or anthracene(2-) anions are sandwiched between ((BDI)-B-DIPeP*)Mg+ and ((BDI)-B-DIPeP)Ca+ cations. These complexes slowly decompose to their homometallic counterparts and further decomposition products. Complexes in which naphthalene(2-) or anthracene(2-) anions are sandwiched between two ((BDI)-B-DIPeP)Ca+ cations were isolated. The low-valent complex (BDI)-B-(DIPeP*)Mg-Ca((BDI)-B-DIPeP) could not be isolated due to its high reactivity. There is, however, strong evidence that this heterobimetallic compound is a fleeting intermediate.
CRIS-Team WoS Importer:2023-05-26

Role of microbiome-gut-brain axis in autism spectrum disorder - Chand, Jagdish; Patel, Neha; Khare, Pragyanshu (Elsevier, 2025)
Autism spectrum disorder (ASD) is a neurological disorder that affects an individual's communication, behavior, and social interaction. Promising treatments specifically targeting the underlying neurophysiology of ASD are currently being developed. In this chapter, we review the pathophysiology and current pharmacological treatment options, along with the detailed role of the gut-brain axis in the ASD phenotype. The review integrates recent findings on the gut microbiota and ASD, addressing potential therapeutic interventions to restore a healthy balance of gut microbiome composition that can improve autism-associated symptoms.
CRIS-Team Scopus Importer:2025-02-28
Keywords: Autism spectrum disorder; Central nervous system; Gut-brain axis; Microbiota